ANALYSIS OF THE INFLUENCE OF PUBLIC PARTICIPATION IN THE MANAGEMENT OF RESOURCES SUSTAINABLE WATER MALANG DISTRICT - Ahmad Kamal Sudrajat; Dewi Nur Arasy; Daning Nindya Fitri Arianti; Sueb Sueb (UNEJ e-Proceeding, 2016)
Water is a major part of the Earth. It is also an important part of life on Earth. It is a natural resource that has limited of both quality and quantity to meet human needs. Based on a survey conducted in the village office, data showed that there are some areas experiencing drought, this area includes four sectors. The purpose of the research is to show influence of public participation in the management of resources sustainable Malang district. The research was conducted in November, 2015 in Malang district. The population is the whole Karangkates village population in Malang district. The sample was 30 people using cluster sampling. The Research instrument is closed questionnaire. Data were analyzed quantitatively in the cross tabulation done by statistical testing with linear regression statistical tests. In conclusion, there is a significant influence of public participation on the management of sustainable water resources in Malang district according to the regression model y= 6,739 + 1,299x with 51.9% reliability models.